Impact of agricultural production outsourcing service and land fragmentation on agricultural non-point source pollution in China: Evidence from Jiangxi Province - Chen, Su; Zhong, Zeyun; Lu, Hua (Frontiers in Environmental Science, 2023)
Agricultural production outsourcing service (APOS) are developing rapidly in China. In-depth research on whether the development of APOS can reduce agricultural nonpoint source pollution (ANSP) and the influencing mechanisms is still lacking. This study analyze the underlying mechanisms and empirically estimate the impact of APOS on ANSP, explore the effect of land fragmentation on the relationship between them, and further empirically test these relationships with microsurvey data on farmers in China. The results reveal that APOS are negatively correlated with excess nitrogen and chemical fertilizer input. APOS use can reduce excess nitrogen and an increase in the number of plots of land leads to an increase in excess nitrogen, and lower the negative effect of APOS on excess nitrogen. APOS affect excess nitrogen by reducing farmers’ input of chemical fertilizers and increasing their adoption of green agricultural production technology. In the future, China should vigorously promote the development of APOS organizations, improve the standardization of outsourcing services to expand the scale of APOS. The government should also strengthen policy support for the construction of field roads, water conservation and irrigation, and should strive to centrally manage scattered land. It is necessary to encourage small-scale farmers to outsource agricultural production activities to the service organizations, thus reducing the negative effect of land fragmentation and increasing the positive effect of APOS in reducing ANSP